Proteasome inhibitor prevents experimental arterial thrombosis in renovascular hypertensive rats - Ostrowska, Justyna K.; Z.Wojtukiewicz, Marek; Chabielska, Ewa; Buczko, Wlodzimierz; Ostrowska, Halina (Thrombosis and Haemostasis, 2004)
Recent studies indicate that highly selective proteasome inhibitors can be useful in prevention of some cardiovascular events. Here we demonstrate that proteasome inhibitor, Z-IleGlu (Ot-Bu) Ala-Leucinal (PSI), is active in the prevention of platelet-dependent arterial thrombosis induced in renovascular hypertensive rats (two-kidney, one clip Goldblatt model, and 2K1C, n=5).The administration of PSI intravenously at a single dose of 0.3 mg/kg before induction of arterial thrombosis markedly increased carotid final flow rate, as compared to control (vehicle) group (10.36 ± 1.8 ml/min and 1.2 ± 1.2 ml/min, respectively), significantly decreased the wet (1.23 ± 0.23 mg and 4.1 ± 0.94 mg, respectively), and dry (0.46 ± 0.145 mg and 1.46 ± 0.39, respectively) thrombus weight, and completely prevented arterial occlusion. Moreover, platelets from PSI treated thrombotic 2K1C rats, showed in response to collagen a significant inhibition of aggregation in the whole blood (10.26 ± 0.6 ohms vs. 15.51 ± 0.91ohms in the control group). In contrast, collagen-induced platelet aggregation was not inhibited in vitro, after pre-treatment of the blood with PSI at the concentration of 10μM that effectively inhibited the 20S proteasome activity in platelets, indicating that ex vivo anti-aggregatory effect of PSI proceeds through an indirect mechanism not associated with suppression of 20S proteasome activity in platelets. In conclusion, our in vivo findings demonstrate that proteasome inhibitor, Z-Ile-Glu(Ot-Bu)Ala-Leucinal, prevents the development of arterial thrombosis in renovascular hypertensive rats and effectively suppresses platelet aggregation by an indirect mechanism. Thus the data provide a new insight into the potential role for the proteasome-dependent pathway in cardiovascular events.
Keywords: Arterial thrombosis; platelet aggregation; proteasome inhibitor; renovascular hypertension; rat